2012
DOI: 10.1111/j.1365-2036.2012.05078.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: the use of carbon dioxide insufflation vs. room air insufflation for gastrointestinal endoscopy

Abstract: SUMMARY BackgroundCarbon dioxide (CO 2 ) insufflation has been proposed as an alternative to air insufflation to distend the lumen in gastrointestinal (GI) endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 32 publications
(308 reference statements)
1
70
2
2
Order By: Relevance
“…This may be due to the rapid absorption of CO2 by the body compared to air. Indeed, CO2 insufflation in esophagogastroduodenoscopy efficiently reduces MWTs by lowering the tension of the gastric mucosa caused by residual gas in the stomach [32] . To our knowledge, the present study is the first RCT to demonstrate the benefit of CO2 insufflation in reducing the risk of MWTs during ESD.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the rapid absorption of CO2 by the body compared to air. Indeed, CO2 insufflation in esophagogastroduodenoscopy efficiently reduces MWTs by lowering the tension of the gastric mucosa caused by residual gas in the stomach [32] . To our knowledge, the present study is the first RCT to demonstrate the benefit of CO2 insufflation in reducing the risk of MWTs during ESD.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies evaluated the safety and efficacy of CO2 insufflation for gastrointestinal endoscopy. Two recent systematic reviews and meta-analysis showed that CO2 insufflation is safe in patients without severe pulmonary disease, and is associated with decreased bowel distension and postprocedural pain [53,54] . Furthermore, one of them showed that insufflation with CO2 in colonoscopy could also decrease abdominal pain during colonoscopy [54] .…”
Section: New Endoscopic Technologies For Colon Examinationmentioning
confidence: 99%
“…CO 2 is absorbed by the bowel mucosa approximately 100 times faster than air and is rapidly eliminated through the lungs (35). This may be associated with the superior recovery quality of CO 2 insufflation compared with room air insufflation in colonoscopy (36). Therefore, when compared with air insufflation, CO 2 insufflation is expected to reduce the volume of residual gas following ESD, which is a primary cause of patient discomfort associated with this procedure, and consequently prevent the development of abdominal symptoms and problems associated with ESD (5,(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%